Analisis Minimalisasi Biaya Antibiotik Pada Pasien Pneumonia Di RSUD Sultan Suriansyah Banjarmasin Periode Januari-Desember 2021: Analisis Minimalisasi Biaya Antibiotik Pada Pasien Pneumonia Di RSUD Sultan Suriansyah Banjarmasin Periode Januari-Desember 2021 - Desy Agustina; Saftia Aryzki; Subhannur Rahman (LPPM Universitas Sari Mulia, 2023)
Background:Pneumonia is an acute lung parenchymal infection which is the second leading cause of death in children after diarrhea. The cost of antibiotic treatment for pediatric pneumonia in 2015 was estimated at US109 million per year. The difference in the cost of antibiotics and other costs incurred by the patient causes the need for pharmacoeconomic analysis with cost minimization analysis methods. Objective:This study aims to determine the minimum antibiotic therapy in pneumonia patients under five at the Sultan Suriansyah Hospital Banjarmasin between ampicillin and ceftriaxone. Methods:A retrospective study with a cross sectional study design through medical records and details of patient financing in the period January - December 2021. Statistical data analysis used was the Independent T-Test and Mann Whitney test. The number of samples in this study was 33 patients with pneumonia in children aged 0-10 years. Result:The results of the study for the average total cost of patient care during hospitalization with the characteristics of patient costs including drug costs, hospitalization costs, doctor visit fees, consultation fees, nutritional services fees, nursing action costs and other supporting costs are Rp 1,872,469 for ampicillin and Rp. 1,709,564 for ceftraixon with p value < 0.05 for the cost of the drug, which means there is a significant difference while the other costs have p > 0.05 which means there is no significant difference between the two drugs. Conclusion:Minimal antibiotic therapy in the treatment of inpatient pneumonia in children is ceftriaxone, with an average cost of Rp. 1,709,564 compared to ampicillin, which is with a total average of Rp. 1,872,469 and there is a significant difference in cost between the two drugs.